2018
DOI: 10.7554/elife.33506
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal LysM receptor ensures robust symbiotic signalling in Lotus japonicus

Abstract: Recognition of Nod factors by LysM receptors is crucial for nitrogen-fixing symbiosis in most legumes. The large families of LysM receptors in legumes suggest concerted functions, yet only NFR1 and NFR5 and their closest homologs are known to be required. Here we show that an epidermal LysM receptor (NFRe), ensures robust signalling in L. japonicus. Mutants of Nfre react to Nod factors with increased calcium spiking interval, reduced transcriptional response and fewer nodules in the presence of rhizobia. NFRe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 60 publications
0
61
0
3
Order By: Relevance
“…Interestingly, Ljsymrk-14, a mutant with defects in an essential GPDC tetra-amino acid motif in the extracellular domain of the receptor, supports nodule organogenesis but not infection (Kosuta et al, 2011). Recently, epidermal Nod Factor Receptor (LjNFR), another LysM-RLK, was found to phosphorylate LjNFR5 and support calcium spiking, nodule initiation, and activation of the TF NIN (Schauser et al, 1999;Murakami et al, 2018).…”
Section: Nod Factor Signaling and The Common Symbiotic Pathwaymentioning
confidence: 99%
“…Interestingly, Ljsymrk-14, a mutant with defects in an essential GPDC tetra-amino acid motif in the extracellular domain of the receptor, supports nodule organogenesis but not infection (Kosuta et al, 2011). Recently, epidermal Nod Factor Receptor (LjNFR), another LysM-RLK, was found to phosphorylate LjNFR5 and support calcium spiking, nodule initiation, and activation of the TF NIN (Schauser et al, 1999;Murakami et al, 2018).…”
Section: Nod Factor Signaling and The Common Symbiotic Pathwaymentioning
confidence: 99%
“…Two of the most potent endogenous plant cytokinins, transzeatin and isopentenyl adenine, were shown to accumulate rapidly upon rhizobial inoculation and in roots exposed to minute amounts of lipo-chitooligosaccharide signalling molecules, known as nodulation factors (NFs) (Van Zeijl et al, 2015;Reid et al, 2016Reid et al, , 2017. Synthesized by rhizobia in the presence of a compatible plant host (Lerouge et al, 1990), NFs initiate symbiotic root development by selectively activating specific plant lysine motif (LysM) receptor-like kinase molecules, known as NF receptors (Limpens et al, 2003;Madsen et al, 2003;Radutoiu et al, 2003Radutoiu et al, , 2007Arrighi et al, 2006;Den Camp et al, 2011;Broghammer et al, 2012;Liang et al, 2014;Murakami et al, 2018). This leads to cellular reprogramming, which drives symbiotic infection and nodule organogenesis (Madsen et al, 2010;Ariel et al, 2012;Singh et al, 2014;Kawaharada et al, 2015Kawaharada et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The proper recognition of rhizobia by the host legume is crucial for a successful symbiosis. To this end, legumes rely on the LysM-domain receptor kinases NFR5 [93], NFR1 [94] and eNFR [7], as well as in the LRR receptor-like kinase SYMRK, to properly detect and decode the NF signal [15][16]. Recently, it was demonstrated that a fourth LysM receptor kinase receptor, EPR3, is required for the perception of compatible rhizobial exopolysaccharides and promotes a successful infection and colonization [95].…”
Section: Expression Of Hormone-and Signal-transduction-related Genes mentioning
confidence: 99%
“…This molecular dialog begins with the detection of legume-derived flavonoids by compatible rhizobia [4][5]. In response, rhizobia produce diffusible nodulation factors (NF), which are perceived by legumes via the LysM-domain receptor kinase Nod Factors Receptor5 (NFR5) and NFR1, both located at the root hair plasma membrane, and likely by the epidermal LysM receptor eNFR [6][7]. Upon NF perception, a wide variety of molecular responses occur, which are crucial to activate the cellular responses required for rhizobial infection and the formation of the new organ termed nodule [8].…”
Section: Introductionmentioning
confidence: 99%